PENGARUH PENAMBAHAN ASAM LAKTAT SEBAGAI ENHANCER TERHADAP PENETRASI PERKUTAN KAFEIN DALAM BASIS GEL - Ameliana, Lidya; Oktora RKS, Lusia; Dwi N, Devi (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2013)
Caffeine is a drug which is effective as an anti-cellulite. Caffeine works by slowing down the lipogenesis process and accelerating the lipolysis process. In this research, caffeine was formulated in Sodium CMC gel base and lactic acid (0, 2, 4, and 6%) as enhancers. The aims of these research was to know the effects of lactic acid as enhancer on pH, viscosity, spreadibility, flowability properties, and percutaneous penetration study of caffeine gel. The results obtained that all formulas have fullfilled of all requirements and it can be concluded that lactic acid lowered the pH, increased viscosity, and lowered spreadibility. The highest flux was obtained the caffeine gel on concentration of 6% lactic acid is equal to 5.43 g/cm2 menit.